2023
DOI: 10.1007/s10029-023-02923-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after open versus robot-assisted repair of ventral hernias: a nationwide database study

N. A. Henriksen,
F. Helgstrand,
K. K. Jensen

Abstract: Purpose The robotic platform is widely implemented; however, evidence evaluating outcomes of robotic ventral hernia repair is still lacking. The aim of the study was to evaluate the short-term outcomes after open and robot-assisted repair of primary ventral and incisional hernias. Methods Nationwide register-based cohort study with data from the Danish Ventral Hernia Database and the National Danish Patients Registry was from January 1, 2017 to August 22, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Although some studies show no significant differences, data from the Nordic countries indicate that robotic-assisted hernia surgery for ventral hernia reduces postoperative pain, shortens hospital stay, accelerates recovery time and ultimately improves patient satisfaction and quality of life compared to open and laparoscopic approaches; [ 3 , 5 , 7 11 ]. The outcomes of robotic-assisted inguinal hernia repair are excellent and comparable with the traditional laparoscopic methods [ 12 , 13 ].…”
Section: Benefits Of Robotic-assisted Hernia Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies show no significant differences, data from the Nordic countries indicate that robotic-assisted hernia surgery for ventral hernia reduces postoperative pain, shortens hospital stay, accelerates recovery time and ultimately improves patient satisfaction and quality of life compared to open and laparoscopic approaches; [ 3 , 5 , 7 11 ]. The outcomes of robotic-assisted inguinal hernia repair are excellent and comparable with the traditional laparoscopic methods [ 12 , 13 ].…”
Section: Benefits Of Robotic-assisted Hernia Surgerymentioning
confidence: 99%
“…However, recent registry and single-centre studies have shown that robotic-assistedhernia repair has emerged as a promising alternative, providing benefits such as improved precision, reduced invasiveness, and better outcomes in terms of less pain, fewer wound complications and a shorter length of stay [ 3 5 ]. Therefore, the integration of robotic hernia surgery represents a significant opportunity to improve surgical practice and patient experience.…”
Section: Introductionmentioning
confidence: 99%